Pengembangan E-Modul Berbasis Multipel Representasi Dengan Bantuan Teknologi Augmented Reality untuk Pembelajaran Materi Bentuk Molekul - Mifta Hurrahman; Erlina Erlina*; Husna Amalya Melati; Eny Enawaty; Rody Putra Sartika (Jurnal Pendidikan Sains Indonesia, 2022)
The integration between the three levels of chemical representations is needed by students to get a comprehensive understanding. Based on the preliminary study only 45.5% out of 120 year 2 and year 3 students of chemistry education who passed the final exam with satisfactory category. Thus, teaching resources that integrate the three levels of chemical representation are needed. The aim of this study is to develop and determine the level of validity of e-module utilizing multiple representations of molecular shapes based on VSEPR theory using augmented reality technology. This research employs research and development refers to the instructional design of the ADDIE model consist of 5 stages: Analyze, Design, Develop, Implementation and Evaluation. The products of this research are the e-module of molecular shapes based on VSEPR theory utilizing multiple representations and Augmented Reality Molecule Simulator (ARMOR) application. The resources presented 13 types of molecular shapes, molecules with lone pair and without lone pair of electrons around the central atom. The instrument used in this study is the validity questionnaire sheet. Data collected were then analyzed using the percentage criteria proposed by Akbar. The results of the experts’ validation indicated that the product is categorized as very valid with 94% of content validity, 93% of media validity, and 99% of language validity. Therefore, the ARMOR is suitable for use in teaching and learning process. Students show a positive response to the use of the application in helping them understand concepts, which are easy to use, has an attractive appearance, and fun.